The Human Microbiome and the Missing Heritability Problem - Sandoval-Motta, Santiago; Aldana, Maximino; Martínez-Romero, Esperanza; Frank, Alejandro (Frontiers in Genetics, 2017)
The "missing heritability" problem states that genetic variants in Genome-Wide Association Studies (GWAS) cannot completely explain the heritability of complex traits. Traditionally, the heritability of a phenotype is measured through familial studies using twins, siblings and other close relatives and making assumptions on the genetic similarities between them. When this heritability is compared to the one obtained through GWAS for the same traits, a substantial gap between both measurements arise and trait-associated genetic variants do not necessarily increase the odds of observing the corresponding trait. Several mechanisms for this “missing heritability” have been proposed, such as epigenetics, epistasis, and sequencing depth. However, none of them are able to fully account for this gap in heritability. In this paper we provide evidence that suggests that in order for the phenotypic heritability of human traits to be broadly understood and accounted for, the compositional and functional diversity of the human microbiome must be taken into account. This hypothesis is based on several observations: A) The composition of the human microbiome is associated with many important traits, including obesity, cancer, and neurological disorders. B) Our microbiome encodes a second genome with nearly a hundred times more genes than the human genome, and this second genome may act as a rich source of genetic variation and phenotypic plasticity. C) Human genotypes interact with the composition and structure of our microbiome, but cannot by themselves explain microbial variation. D) Microbial genetic composition can be strongly influenced by the host’s behavior, its environment or by vertical and horizontal transmissions from other hosts. Therefore, genetic similarities assumed in familial studies may cause overestimations of the heritability. In this paper we propose that the compositional and functional diversity of our microbiome can and must be incorporated to current genome wide association studies to gain a broader understanding of the heritability of human traits.